Maxillary tooth displacement in the infratemporal fossa - Korosh Roshanghias; Andre Peisker; Jorg Olaf Zieron (Wolters Kluwer Medknow Publications, 2016)
Wisdom tooth operations are sometimes accompanied by complications. This case report shows complications during upper jaw third molar removal. Expectable problems during oral surgery should be planned to be solved in advance. Displacement of the third molar during oral surgeries as a considerable complication is rarely discussed scientifically. A good design of flap, adequate power for extraction, and clear view on the surgical field are crucial. Three-dimensional radiographic diagnostics in terms of cone beam computed tomography is helpful after tooth displacement into the infratemporal fossa.